Understanding the importance of peak bone mass - Timothy Hereford, MD; Alec Kellish, MD; Julie Balch Samora, MD, PhD; Louise Reid Nichols, FAOA, FAAOS, MD (Elsevier, 2024)
ABSTRACT: Bone mass attained early in life is one of the most important determinants of lifelong skeletal health. Bone mineral content increases exponentially during childhood. In fact, 40%-60% of the total adult bone mass is accrued during puberty. By the end of the first 2 decades of life, peak bone mass has been reached. Between ages 20-50, bone mass has plateaued, but it continues to remodel. This is regulated by parathyroid hormone (PTH), vitamin D3, and insulin-like growth factor 1 (IGF-1). After the age of 50, bone mass begins to decrease. The purpose of this paper is to review the importance of maximizing peak bone mass and factors that can modify and maintain peak bone mass. Key Concepts: (1) Peak bone mass is attained by the end of the second decade of life. (2) There are more fractures during peak height velocity in adolescence as the body increases in size but bone mineralization lags behind. (3) The risk of adult osteoporosis starts in childhood. (4) There are modifiable and nonmodifiable risk factors that affect peak bone mass. Level of Evidence: IV